Rising earnings inequality in Sweden: The role of composition and prices - David Domeij (Stockholm School of Economics, The Economic Research Institute (EFI), 2006)
This paper decomposes the rise in cross-sectional earnings inequality in Sweden between 1990 and 2002 into changes in market prices of observable characteristics, changes in the composition of the labor force across demographic groups and industries, and changes in unobservables, and compares the Swedish experience with that in the U.S. The rise in earnings inequality is in both countries a consequence of rising upper tail dispersion. Contrary to the U.S. experience, where the rise is largely driven by changing market prices of observables and increased residual dispersion, shifts in the Swedish labor force composition have contributed positively to the rise in the P90-P50 gap. The rise in the Swedish P99-P90 gap is however entirely accounted for by changes in prices and residual dispersion.
Keywords: E24; J31; 330; Earnings; inequality; Sweden; United States; Einkommensverteilung; Erwerbspersonenpotenzial; Vergleich; Schweden; USA